Показники розвитку сільських районів і сприяння веденню сталого сільського господарства - Ільченко, В.М.; Малоок, І.А. (Культура народов Причерноморья, 2014)
У статті проаналізовано показники розвитку сільських районів, здійснено аналіз деяких
проблем у сфері сільського господарства та запропоновано можливі шляхи вирішення цих проблем, не
відкидаючи досвіду іноземних країн. Увагу сконцентровано на необхідності переходу України до сталого
сільського господарства для покращення не лише показників виробництва, а й соціально-економічної та
демографічної ситуації на селі. В статье проанализированы показатели развития сельских районов, осуществлен анализ
некоторых проблем в сфере сельского хозяйства и предложены возможные пути решения этих проблем,
не отвергая опыта зарубежных стран. Внимание сконцентрировано на необходимости перехода
Украины к устойчивому сельскому хозяйству для улучшения не только показателей производства, но и
социально-экономической и демографической ситуации на селе. The paper analyzes the performance of rural areas, the analysis of some problems in agriculture and
suggests possible solutions to these problems, while not rejecting the experience of foreign countries. Analyzed
indicators are indexes and structure of gross agricultural production; proportion of crop and livestock
production in gross agricultural production; contribution of the main categories of producers in the production
of gross agricultural production; proportion and location of regions in total gross production of agriculture,
ranking regions for growth, lower gross agricultural production. Important problems included the degradation
of rural areas; extensive farming, which causes intense development of erosion processes; decline in the share of
gross agricultural crop production; inadequate care of the state as the agricultural sector. The ways to
overcome the problems identified development of alternative methods of farming; improvement in reducing the
volume of soil application of Chemicals through the introduction of Biologicals; attracting foreign and domestic
investment in the agricultural sector of the economy of Ukraine. Attention is focused on the need for Ukraine's
transition to sustainable agriculture to improve performance not only production, but also socio-economic and
demographic situation in rural areas.